1988
DOI: 10.1128/aac.32.6.873
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities to antibiotics and antiseptics of new species of the family Enterobacteriaceae

Abstract: One hundred and sixty-nine strains of new species of the family Enterobacteriaceae, isolated mainly from the environment, were tested to determine their susceptibilities to 13 antibiotics and 4 antiseptics or disinfectants. All the species were susceptible to aminoglycosides, doxycycline, and trimethoprim but were resistant to chloramphenicol. Susceptibility to ,-lactams varied more among the strains. However, all the strains were cefotaxime susceptible, apart from some Buttiauxella agrestis strains for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 9 publications
1
19
0
1
Order By: Relevance
“…Because of higher MIC values to all â-lactam agents it is likely that the strains included in the latter study showed an increased â-lactamase expression compared with strains in the present study. Comparison of the results of the present study with those of the study by Freney et al [27], by examining the antibiotic susceptibility of K. terrigena and K. planticola, could lead to erroneous conclusions, because only MIC50 and MIC90 values were cited. Nevertheless, the MICs of ampicillin for 90% of K. planticola strains in this study were 4 mg=L, which would correlate with the natural ampicillin sensitivity of the species.…”
Section: Discussionmentioning
confidence: 64%
“…Because of higher MIC values to all â-lactam agents it is likely that the strains included in the latter study showed an increased â-lactamase expression compared with strains in the present study. Comparison of the results of the present study with those of the study by Freney et al [27], by examining the antibiotic susceptibility of K. terrigena and K. planticola, could lead to erroneous conclusions, because only MIC50 and MIC90 values were cited. Nevertheless, the MICs of ampicillin for 90% of K. planticola strains in this study were 4 mg=L, which would correlate with the natural ampicillin sensitivity of the species.…”
Section: Discussionmentioning
confidence: 64%
“…Such changes, in the case of the Providencia isolates, were thought to affect binding of the biguanides to the cell surface and therefore reflected envelope modification (74). Freney et al (82) found no evidence of decreased susceptibility within 169 novel Enterobacteriaceae isolated from the general environment relative to clinical isolates. Arguably, such studies support the view that antiseptic use in hospitals does not contribute to the biocide susceptibilities of enterococcal isolates.…”
Section: Possible Associations Between Biocide Use and Resistance-fiementioning
confidence: 99%
“…After 24 h of incubation at either 37°C (Enterobacteriaceae) or 30°C (Aeromonas), organisms were classified as sensitive, intermediate, or resistant according to French national guidelines (17). Acquired resistances were deduced from data on wild-type antibiotic susceptibility patterns characteristic of each species (17,19,37,40). Strains with a decreased susceptibility were considered low-level resistant.…”
mentioning
confidence: 99%